Analisis Kualitas Air Desa Nulle Kecamatan Amanuban Barat Kabupaten Timor Tengah Selatan - Malino, Maria G. O.; Kadang, Luther (Chemistry Notes, 2022)
The importance of the role of water in life makes water conditions must be maintained both quantity and quality given the growing human life that also has an impact on the environment. The purpose of this study was to find out the condition and status of water contamination in springs used as drinking water in Nulle village, West Amanuban subdistrict, South Central Timor district. The method of collecting data is obtained from the field. The technique used to determine the location of sampling is the purposive sampling technique. The data collection stage is carried out by conducting initial surveys, determining sampling points, water sampling, examination of water samples in that way (directly) on temperature and pH parameters and in ex (laboratory) on the parameters of TDS, TSS, hardness, detergent, DO, COD and total coliform. The results of the study on both springs showed the value of each of the parameters tested was still within safe limits based on the Regulation of the Minister of Health of the Republic of Indonesia No. 32 of 2017 on Environmental Health Quality Standards and Water Health Requirements for Hygiene, Sanitation, Swimming Pool, Solus Per Aqua and Public Baths except the total coliform parameters in both springs that exceeded the quality standard by 50 amount / 100 mL according to. The average total coliform rate at station 1 is 50.33 total/100 mL and the average at station 2 is 107.67 total/100 mL. The status of water contamination at both stations based on the STORET method is moderate contamination.